2021
DOI: 10.1186/s13063-021-05454-8
|View full text |Cite
|
Sign up to set email alerts
|

Placebo response and effect in randomized clinical trials: meta-research with focus on contextual effects

Abstract: Background Contextual effects (i.e., placebo response) refer to all health changes resulting from administering an apparently inactive treatment. In a randomized clinical trial (RCT), the overall treatment effect (i.e., the post-treatment effect in the intervention group) can be regarded as the true effect of the intervention plus the impact of contextual effects. This meta-research was conducted to examine the average proportion of the overall treatment effect attributable to contextual effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 96 publications
4
53
0
2
Order By: Relevance
“…These systemic and non-specific factors could contribute to an increased improvement following SMT. The same has been observed in acupuncture 55 and exercise 56 , and it is a general finding across multiple interventions 57 . The same argument can be made for SMT in general, as it is non-superior to non-thrust mobilization or even sham SMT 58 .…”
Section: Discussionsupporting
confidence: 62%
“…These systemic and non-specific factors could contribute to an increased improvement following SMT. The same has been observed in acupuncture 55 and exercise 56 , and it is a general finding across multiple interventions 57 . The same argument can be made for SMT in general, as it is non-superior to non-thrust mobilization or even sham SMT 58 .…”
Section: Discussionsupporting
confidence: 62%
“…a situation where a negative outcome occurs owing to a belief that the intervention will cause harm) represent complex and distinct psychoneurobiological phenomena, in which behavioural and neurophysiological changes follow the application of a treatment [ 32 ]. The therapist and the patient’s characteristics, the patient–therapist relationship and the characteristics of the treatment are all contextual factors influencing clinical outcomes [ 32 , 33 ]. Thus, when evaluating the effectiveness of treatments, the importance of patients’ expectations, feelings and clinical context should not be ignored [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The therapist and the patient’s characteristics, the patient–therapist relationship and the characteristics of the treatment are all contextual factors influencing clinical outcomes [ 32 , 33 ]. Thus, when evaluating the effectiveness of treatments, the importance of patients’ expectations, feelings and clinical context should not be ignored [ 33 ]. The placebo effect might have played a role in participants’ appraisal of arthritis glove wearing, because both gloves were prescribed and fitted by rheumatology occupational therapists in a hospital setting, and the placebo/control gloves had the credible appearance of arthritis gloves.…”
Section: Discussionmentioning
confidence: 99%
“…50 The effects observed in the present trial across different outcomes may be a small specific effect of exercise and/or of other contextual factors. It could be caused by contact with healthcare professionals [58][59][60] , regression to the mean, natural cause of the disease, 61 or simply by placebo effect 50 -making it difficult to ascribe too much specific cause-of-effect to exercise therapy. In line with this, the recent DISCO trial found equivalent improvements after a supervised exercise and education program, and saline injections in patients with knee OA.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…This re-evaluation based on symptom changes, combined with additional attention from an orthopedic surgeon, could have facilitated the patients' decision to postpone surgery. [58][59][60][65][66][67][68] This is exemplified in table 4 showing that patients who believe they need surgery, undergo surgery, while those who "don't know" or do not believe they need surgery postpone it.…”
Section: Secondary Outcomesmentioning
confidence: 99%